15‐1: Flat Type Transparent Display Demonstrating Field‐Sequential‐Color. Issue 1 (May 2016) - Kuo, Chia‐Wei; Liao, Yi‐Yang; Tseng, Bo‐Shiang; Yu, Tun‐Hao; Hsieh, Hsiang‐Yuan; Lin, Jhuang‐Yue; Lin, Ching‐Huan; Lai, Yi‐Hsiang; Chuang, Chin‐Tang; Yeh, Cheng‐Nan; Sugiura, Norio
Abstract : In this paper, a 10.1″ color filter‐less liquid crystal display (LCD) with transparent light guide has been developed for transparent LCD (T‐LCD) application. LED light sources could create four primary‐color fields R‐G‐B‐W rapidly flashing to satisfy field‐sequential‐color (FSC) method. Finally, this prototype could demonstrate a high NTSC and transparency scenario.